PEMANFAATAN MUSEUM NEGERI âBALANGAâ SEBAGAI MEDIA PEMBELAJARAN DI KALIMANTAN TENGAH - Azis, Abdul (LP2M IAIN Palangka Raya, 2013)
Everything that mediates learning is it in the form of objects, people, environments, or experiences that contain the value of learning and to stimulate the studets for learning, include, learning media. State Museum